Hydrogen Sulfide Confers Lung Protection During Mechanical Ventilation via Cyclooxygenase 2, 15-deoxy Δ12, 14-Prostaglandin J2, and Peroxisome Proliferator-Activated Receptor Gamma. Issue 8 (August 2017) - Spassov, Sashko G.; Faller, Simone; Hummel, Matthias; Helo, Khaled; Ihle, Andreas; Ryter, Stefan W.; Strosing, Karl M.; Hoetzel, Alexander
Abstract : Objectives: Hydrogen sulfide reduces ventilator-induced lung injury in mice. Here, we have examined the underlying mechanisms of hydrogen sulfide-mediated lung protection and determined the involvement of cyclooxygenase 2, 15-deoxy Δ 12, 14 -prostaglandin J2, and peroxisome proliferator-activated receptor gamma in this response. Design: Randomized, experimental study. Setting: University medical center research laboratory. Subjects: C57BL/6 mice and in vitro cell catheters. Interventions: The effects of hydrogen sulfide were analyzed in a mouse ventilator-induced lung injury model in vivo as well as in a cell stretch model in vitro in the absence or presence of hydrogen sulfide. The physiologic relevance of our findings was confirmed using pharmacologic inhibitors of cyclooxygenase 2 and peroxisome proliferator-activated receptor gamma. Measurements and Main Results: Mechanical ventilation caused significant lung inflammation and injury that was prevented in the presence of hydrogen sulfide. Hydrogen sulfide-mediated protection was associated with induction of cyclooxygenase 2 and increases of its product 15-deoxy Δ 12, 14 -prostaglandin J2 as well as cyclooxygenase 2/15-deoxy Δ 12, 14 -prostaglandin J2-dependent activation of peroxisome proliferator-activated receptor gamma. Hydrogen sulfide-dependent effects were mainly observed in macrophages. Applied mechanical stretch to RAW 264.7 macrophages resulted in increased expression of interleukin receptor 1 messenger RNA and release of macrophage inflammatory protein-2. In contrast, incubation of stretched macrophages with sodium hydrosulfide prevented the inflammatory response dependent on peroxisome proliferator-activated receptor gamma activity. Finally, application of a specific peroxisome proliferator-activated receptor gamma inhibitor abolished hydrogen sulfide-mediated protection in ventilated animals. Conclusions: One hydrogen sulfide-triggered mechanism in the protection against ventilator-induced lung injury involves cyclooxygenase 2/15-deoxy Δ 12, 14 -prostaglandin J2-dependent activation of peroxisome proliferator-activated receptor gamma and macrophage activity. Abstract : Supplemental Digital Content is available in the text.